UJI EFEKTIVITAS INSEKTISIDA NABATI BERBAHAN BIJI MIMBA (Azadiractha indica A. Juss) DAN LIMBAH DAUN TEMBAKAU (Nicotiana tabacum L.) UNTUK MENGENDALIKAN Spodoptera litura F. - Avrida Kristiawan; Suharto Suharto; Wildan Jatmiko (Berkala Ilmiah Pertanian, 2019)
ABSTRACT Spodoptera litura F. is a pest that causes a decrease in production at various plant phases. S litura attacks the leaves and fruit of the plant, causing leaves to be slightly whitish because only the upper leaves are left behind. The cause of the high attack of pests is resistance to the use of chemical insecticides that are used continuously. The negative impact of the use of chemical insecticides can be reduced by the use of vegetal insecticides made from neem seeds and tobacco leaf waste. The study was conducted in May to June 2017, through two stages. The first stage is preparation includes the multiplication and maintenance of S litura, tool sterilization, and extraction of vegetal insecticides in the Laboratory of Pests and Diseases. The second stage of preparation includes the application of vegetal insecticides to S litura. The application of the treatment uses factorial Randomized Complete Design (RAL) with the first factor, which is neem seed (M), and vegetal insecticides made from tobacco leaf waste (T) and the second factor Concentration (D) includes 5 concentrations namely 15%, 12.5%, 10%, 7.5%, 5% plus controls as a comparison with an accuracy value of 95% and continued Duncan test 95%. The combination of treatment was the concentration of pulp seeds of 15%, neem seed concentration of 12.5%, neem seed concentration of 10%, neem seed concentration of 7.5%, pulp concentration of 5%, tobacco leaf waste concentration of 15%, tobacco leaf waste concentration of 12.5 %, 10% tobacco leaf waste concentration, 7.5% tobacco leaf waste concentration, 5% tobacco leaf waste concentration. Neem seeds are the best vegetal insecticides to control as many as S litura pests. The best concentration to increase production is 15%. Keywords : Tabacco Leaf Waste, Neem Seeds, Concentration, S. litura F. ABSTRAK Spodoptera litura F. merupakan hama pemakan daun hingga habis, sehingga hanya tertinggal bagian epidermis daun dan tulang-tulang daun saja (Kurmia, 2017). Penyebab tingginya serangan hama ini dikarenakan karena resistensi hama akibat penggunaan insektisida kimia yang digunakan secara terus menerus. Penelitian dilakukan pada bulan Mei sampai Juni 2017, melalui dua tahap. Tahap pertama adalah persiapan meliputi perbanyakan dan pemeliharaan S litura, sterilisasi alat, dan ektraksi insektisda nabati Labolatorium Hama dan Penyakit. Tahap kedua persiapanya meliputi aplikasi insektisida nabati pada S litura. Pengaplikasian perlakuan menggunakan Rancangan Acak Lengkap (RAL) faktorial dengan faktor pertama yaitu insketisida nabati berbahan biji mimba (M), dan insektisida nabati berbahan limbah daun tembakau (T) dan faktor kedua Konsentrasi (D) meliputi 5 konsentrasi yaitu 15%, 12,5%, 10%, 7,5%, 5% ditambah kontrol sebagai pembanding dengan nilai ketepatan 95% dan dilanjutkan uji Duncan 95%. Kombinasi perlakuan yaitu konsentrasi biji mimba 15%, konsentrasi biji mimba 12,5%, konsentrasi biji mimba 10%, konsentrasi biji mimba 7,5%, konsentrasi mimba 5%, konsentrasi limbah daun tembakau 15%, konsentrasi limbah daun tembakau 12,5%, konsentrasi limbah daun tembakau 10%, konsentrasi limbah daun tembakau 7,5%, konsentrasi limbah daun tembakau 5%. Kata Kunci : Limbah Daun Tembakau, Biji Mimba, Konsentrasi, dan S. litura F